Outcomes and measures of delirium interventional studies in palliative care to inform a core outcome set: A systematic review. (December 2021) - Agar, Meera R; Siddiqi, Najma; Hosie, Annmarie; Boland, Jason W; Johnson, Miriam J; Featherstone, Imogen; Lawlor, Peter G; Bush, Shirley H; Page, Valerie; Amgarth-Duff, Ingrid; Garcia, Maja; Disalvo, Domenica; et al.
Background: Trials of interventions for delirium in various patient populations report disparate outcomes and measures but little is known about those used in palliative care trials. A core outcome set promotes consistency of outcome selection and measurement. Aim: To inform core outcome set development by examining outcomes, their definitions, measures and time-points in published palliative care studies of delirium prevention or treatment delirium interventions. Design: Prospectively registered systematic review adhering to Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Data sources: We searched six electronic databases (1980–November 2020) for original studies, three for relevant reviews and the International Clinical Trials Registry Platform for unpublished studies and ongoing trials. We included randomised, quasi-randomised and non-randomised intervention studies of pharmacological and non-pharmacological delirium prevention and/or treatment interventions. Results: From 13/3244 studies (2863 adult participants), we identified 9 delirium-specific and 13 non-delirium specific outcome domains within eight Core Outcome Measures in Effectiveness Trials (COMET) taxonomy categories. There were multiple and varied outcomes and time points in each domain. The commonest delirium specific outcome was delirium severity ( n = 7), commonly using the Memorial Delirium Assessment Scale (6/8 studies, 75%). Four studies reported delirium incidence. Non-delirium specific outcomes included mortality, agitation, adverse events, other symptoms and quality of life. Conclusion: The review identified few delirium interventions with heterogeneity in outcomes, their definition and measurement, highlighting the need for a uniform approach. Findings will inform the next stage to develop consensus for a core outcome set to inform delirium interventional palliative care research.